Metode Project-Based Learning untuk Meningkatkan Hasil Belajar IPA Materi Siklus Air Bagi Siswa Kelas V Sekolah Dasar - Tria Nency (Direktorat Guru Pendidikan Dasar, Kemendikbudristek R.I., 2023)
This study aims to examine to what extent that project based learning improves student learning outcomes in learning science about water cycles. This is a classroom action research with two cycles conducted in the fifth grade class in an private primary school. The author collected data by conducting evaluation tests and classroom observation in learning the water cycle material. The instruments used are evaluation test and observation sheets. To analyze the data in this study using qualitative and quantitative data analysis techniques. The findings show that there is an increase in learning outcomes from cycle 1 (average score 73) and cycle 2 (average score 86). These findings indicate that the application of project-based learning for the water cycle material in science subjects has proven effective in increasing learning outcomes and students’ participation. The results can certainly be used by primary school teachers as a reference in teaching water cycle material or other related materials in science subjects. In addition, of course, this study reports on how to apply empirically the application of project-based learning as a variation of student-centered learning methods and promote student participation and collaboration, especially in science subjects.